A rapid UHPLC–MS/MS method for the quantification of ARQ531 in rat plasma: Validation and its application to a pharmacokinetic study. (14th July 2020) - Liu, Jizhen; Ji, Musi; Li, Zhidong; Xu, Xun; Li, Lili; Li, Huawen; Tian, Yuguang; Su, Xiaohua
Abstract: A simple and sensitive ultra‐high performance liquid chromatography–tandem mass spectrometric (UHPLC–MS/MS) method was developed and validated for the determination of ARQ531, a Bruton's tyrosine kinase inhibitor in rat plasma. After protein precipitation with acetonitrile, the samples were separated on a UPLC BEH C18 column with 0.1% formic acid in water and acetonitrile as mobile phase at a flow rate of 0.4 ml/min. The mass detection was performed on a triple quadrupole tandem mass spectrometer by multiple reaction monitoring with precursor‐to‐product ion transitions of m/z 479.1 > 365.1 and m/z 441.2 > 138.1 for ARQ531 and internal standard, respectively. Good linearity (correlation coefficient > 0.9988) was achieved over the concentration range of 0.5–1, 000 ng/ml and the lower limit of quantitation was 0.5 ng/ml. The accuracy ranged from −13.50 to 11.35% and the precision was <8.87%. The extraction recovery was >85.56%. ARQ531 was demonstrated to be stable under the tested conditions. The validated method was further applied to a pharmacokinetic study of ARQ531 in rats after intravenous (1 mg/kg) and oral (1, 3 and 10 mg/kg) administration. The results demonstrated that ARQ531 displayed linear pharmacokinetic profiles over the oral dose range of 1–10 mg/kg and good oral bioavailability (>50%).